A STUDY OF AQUATIC OLIGOCHAETES COMMUNITY IN THE UPPER PART OF AL- ABBASYIA RIVER / MIDDIE OF IRAQ - & Jawair, Al- Ameen (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
In the current study aquatic oligochaetes worms were collected monthly from five sites along AL- Abbasyia  river / Al-Najaf province, South Iraq for a period between February 2018 to  January 2019. Physical and chemical parameters for river water were examined which include: Air and Water temperature, pH ,Electrical conductivity ,Salinity, Dissolved oxygen , Biological oxygen demand and Sediment texture. The results showed a number of 5039 individuals of aquatic Oligochaeta were identified as three families Naididae ,Lumbriculdae and Enchytraaeidae .Tow species of Naididae Allonais pectinata (Stephenson, 1910)  and Dero (Dero) dorsalis Forroniere, 1899 are considered as a new records in Euphrates River . Results showed the site S4 was highest number of worms site, 1323 worms of 17 species were found, while the lowest number of 579 individuals of 11 species were recorded in S2. J-card index for similarity showed that the highest similarity was between site S2 and site S3. Temporally, the highest individual numbers were recorded during September, while in April the lowest individual's number was recorded.